Socioeconomic differences in food habits among 6‐ to 9‐year‐old children from 23 countries—WHO European Childhood Obesity Surveillance Initiative (COSI 2015/2017) - Fismen, Anne‐Siri; Buoncristiano, Marta; Williams, Julianne; Helleve, Arnfinn; Bakacs, Márta; Bergh, Ingunn Holden; Duleva, Vesselka; Fijałkowska, Anna; Gualtieri, Andrea; Hejgaard, Tatjana; Hyska, Jolanda; Kelleher, Cecily C.; et al. (Wiley, 2021)
Background Socioeconomic differences in children's food habits are a key public health concern. In order to inform policy makers, cross-country surveillance studies of dietary patterns across socioeconomic groups are required. The purpose of this study was to examine associations between socioeconomic status (SES) and children's food habits. Methods The study was based on nationally representative data from children aged 6–9 years (n = 129,164) in 23 countries in the World Health Organization (WHO) European Region. Multivariate multilevel analyses were used to explore associations between children's food habits (consumption of fruit, vegetables, and sugar-containing soft drinks) and parental education, perceived family wealth and parental employment status. Results Overall, the present study suggests that unhealthy food habits are associated with lower SES, particularly as assessed by parental education and family perceived wealth, but not parental employment status. We found cross-national and regional variation in associations between SES and food habits and differences in the extent to which the respective indicators of SES were related to children's diet. Conclusion Socioeconomic differences in children's food habits exist in the majority of European and Asian countries examined in this study. The results are of relevance when addressing strategies, policy actions, and interventions targeting social inequalities in children's diets.